Above the glass ceiling: When are women and racial/ethnic minorities promoted to CEO?. (26th July 2013) - Cook, Alison; Glass, Christy
<x xml:space="preserve">Abstract</x> Using a dataset of all CEO transitions in Fortune 500 companies over a 15‐year period, we analyze mechanisms that shape the promotion probabilities and leadership tenure of women and racial/ethnic minority CEOs. Consistent with the theory of the glass cliff, we find that occupational minorities—defined as white women and men and women of color—are more likely than white men to be promoted CEO of weakly performing firms. Though we find no significant differences in tenure length between occupational minorities and white men, we find that when firm performance declines during the tenure of occupational minority CEOs, these leaders are likely to be replaced by white men. We term this phenomenon the "savior effect." © 2013 John Wiley & Sons, Ltd.